1978
DOI: 10.1007/bf01408202
|View full text |Cite
|
Sign up to set email alerts
|

ExperimentalQ ?-values of several short-lived nuclides with mass number 85?A?103

Abstract: The Q~-values of 85'86Se, 9~ 93Kr, m~ and 1~ were measured using massseparated sources produced at the on-line mass separator LOHENGRIN. The experimental values are compared with mass formula predictions. Taking also into account earlier results, a subshell-closure effect for the neutron number N=56 and proton number Z = 38 is shown to exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Table 2. This value agrees well with the one measured by us in an earlier experiment [5]. The weighted mean value calculated from the results of both experiments is Qe = 5530 ___ 30 keV, cf.…”
Section: ~supporting
confidence: 83%
“…Table 2. This value agrees well with the one measured by us in an earlier experiment [5]. The weighted mean value calculated from the results of both experiments is Qe = 5530 ___ 30 keV, cf.…”
Section: ~supporting
confidence: 83%
“…The previously adopted levels [10] at 102.7 and 641 keV are also seen in the present studies. Special attention was paid to the determination of the intensity of the 241 keV line because of its importance for the discussion (see below).…”
Section: L~176mentioning
confidence: 86%
“…A 102.4 keV line was also observed by Ahrens et al [9] in the /3-decay of l~ for which a half-life of (1.5_+0.2)s was reported. Berg et al [10] studied the /~-decay of l~ They found 7 transitions of 103, 126, 538 and 641 keV and deduced a value of Q~ = (5,500 +_120) keV for this decay. Seli~ et al [11] reported a lifetime of tl/2=(1.7 _+0.3)ns for the 103 keV level.…”
Section: Introductionmentioning
confidence: 97%